(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the factors associated with morbidity and mortality from acquired immunodeficiency syndrome (AIDS) in people deprived of their liberty. Methodology: This is an integrative literature review, with searches in the database: Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval System Online (Medline) and Latin American and Caribbean Literature in Health Sciences (Lilacs). The descriptors used consisted of "Acquired Immunodeficiency Syndrome" and "Prison", combined with the boolean operator AND. The inclusion criteria considered studies referring to the period between 2018 and 2023, available in full. Articles not related to the proposed topic were excluded. Results: Considering the criteria set out, 11 articles were selected, among the 58 found. Discussion: Health aspects were highlighted, emphasizing the association between AIDS morbidity and variables such as hepatitis, tuberculosis, drug abuse and co-infections. Social, economic, and educational factors were also addressed, indicating the impact of overcrowded prisons, low socioeconomic status, and lack of sexual education. The analysis of the selected literature highlights the vulnerability of incarcerated individuals and the need for specific attention to prevent the spread of HIV. Conclusion: HIV morbidity and mortality in prisons is related to health, economic and social factors, including risky practices such as tattoos and needle sharing. The need for additional research to understand the epidemiological profile is highlighted.